Analysis of the Potential Leading Sectors of Cirebon Regency as a Buffer Area in the Rebana Metropolitan Area - Andis Destrian Irianto; Hana Helmalia Fitri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Rebana Metropolitan Area is designed as an economic growth center in the northeastern part of West Java by emphasizing integrated and sustainable investment. Cirebon Regency acts as a buffer zone as well as an Industrial Designation Area (KPI) which has great potential in supporting regional economic growth. This study aims to identify the leading sectors of Cirebon Regency that can be optimized in regional economic development. The method used is quantitative descriptive analysis with the Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Klassen Typology approaches to identify base sectors and prospective sectors. The results of the analysis show that Cirebon Regency has nine basic sectors and eleven prospective sectors that have the potential for further development. Some of the main sectors, such as manufacturing industry, trade, and agriculture, still face challenges of competitiveness and integration with other regions in the Rebana Region. Therefore, a development strategy is needed that focuses on strengthening developing sectors to become leading sectors and encouraging underdeveloped sectors to transform to become more competitive. In conclusion, optimizing the leading sectors in Cirebon Regency can support more sustainable economic growth in the Rebana Metropolitan Area through targeted economic planning.